1970
DOI: 10.1002/jcp.1040750210
|View full text |Cite
|
Sign up to set email alerts
|

The possible mediation by cyclic AMP of parathyroid hormone‐induced stimulation of mitotic activity and deoxyribonucleic acid synthesis in rat thymic lymphocytes

Abstract: Purified parathyroid hormone (PTH) strongly stimulates the initiation of deoxyribonucleic acid (DNA) synthesis and thereby raises the flow of cells into mitosis in rat thymic lymphocyte populations maintained i n vitro. These actions of PTH are potentiated by caffeine and inhibited by imidazole which indicates that the hormonal action is mediated by cyclic adenosine 3',5',-monophosphate (cyclic AMP). The feasibility of cyclic AMP being the mediator of PTH action is established by the observation that a low con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Furthermore, at least one instance in which T cells or a thymic factor (or both) control bone resorption in vivo has been reported in the literature (34,35): osteopetrotic (op/op) rats, in which osteoclasts are present but not active, have been shown to resume normal osteoclastic bone resorption when injected with normal thymic cell suspensions, therefore also raising the possibility of a role for the T lymphocytes in osteoclast activation, both in vivo and in vitro. Finally, T lymphocytes have been shown to have receptors for PTH (36,37), calcitonin (38), and 1,25-(OH)2-vitamin D3 (39), the three major calcium-regulating hormones with specific effects on bone cells and bone remodeling; vitamin D metabolites have also been shown to have marked effects on the differentiation of cells of the Proc. NatL Acad Sci.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at least one instance in which T cells or a thymic factor (or both) control bone resorption in vivo has been reported in the literature (34,35): osteopetrotic (op/op) rats, in which osteoclasts are present but not active, have been shown to resume normal osteoclastic bone resorption when injected with normal thymic cell suspensions, therefore also raising the possibility of a role for the T lymphocytes in osteoclast activation, both in vivo and in vitro. Finally, T lymphocytes have been shown to have receptors for PTH (36,37), calcitonin (38), and 1,25-(OH)2-vitamin D3 (39), the three major calcium-regulating hormones with specific effects on bone cells and bone remodeling; vitamin D metabolites have also been shown to have marked effects on the differentiation of cells of the Proc. NatL Acad Sci.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition o f E rosette formation by P T H was also reported by Giacchino et al However, other investigators claimed that PT H has a stimulatory effect on T lymphocytes. PTH-induced stim ulation of mitotic activity and deoxyribonucleic acid syn thesis in rat T cells was reported in 1977 by Whitefield et al [25] who assumed that this action is mediated via cA M P . Perry [26] found that the amino-terminal frag ment activates mononuclear leukocytes, causing them to produce a substance that enhances bone resorption.…”
Section: Effect Of Pth On T Cellsmentioning
confidence: 99%
“…Various hormones, and elevated concentrations of calium and magnesium, have been shown to exert a mitogenic action on thymus lymphocytes Youdale 1969, Whitfield, Perris and. The hormone action is dependent on the availability of calcium, but can be mimicked by c-AMP (Whitfield, MacManus and Rixon 1970) and apparently is due to a stimulation of the entry of cells into the DNA-synthetic S-phase of the cycle. Radiation-induced mitotic delay in these cells has also been found to be diminished by the same agents and mechanism of action (Whitfield, Rixon and Youdale 1969).…”
Section: Introductionmentioning
confidence: 99%